ANALISIS PERLAKUAN AKUNTANSI ASET BIOLOGIS TINJAUAN TEORITIS ADOPSI IAS 41 - Nur Afni Yunita; Nur Ramadani (Faculty of Economics and Business, Universitas Malikussaleh, 2019)
This study animed to determine how the treatment of biological assets in PTPN IV and the comparison of the tretment of biological assets based on the standars applied by PTPN IV with IAS 41. The objects in this study were the treatment of biological assets in PTPN IV. The research method used was descriptive qualitative research. The reseults of this study indicated that the recongnition, presentation, and disclosure for biological assets at PTPN IV was in accordance with IAS 41, but for measuring biological assets using the acquisition price while IAS 41 measures biological assets using fair value.